1995
DOI: 10.2807/esm.00.00.00125-en
|View full text |Cite
|
Sign up to set email alerts
|

Cholera in the Mediterranean: outbreak in Albania

Abstract: In the 1990s, an epidemic of cholera caused by Vibrio cholerae 01 El Tor has spread from northern Pakistan to the Mediterranean. In 1993 sporadic cases of cholera, and epidemic foci, were recorded in many countries of the southern part of Eastern Europe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…However, it should be noted that a survey on drinking water quality in the area of Tirana (the capital of Albania) showed the presence of microorganisms in one-third of water samples, whereas one fifth had no residual chlorine [27]. This suggests the possibility of waterborne transmission not only for viral and bacterial infectious agents [3,8], but also for intestinal parasites. Water contamination in this country is the consequence of the discharge of untreated urban and industrial wastewater directly into rivers, lakes or seas.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…However, it should be noted that a survey on drinking water quality in the area of Tirana (the capital of Albania) showed the presence of microorganisms in one-third of water samples, whereas one fifth had no residual chlorine [27]. This suggests the possibility of waterborne transmission not only for viral and bacterial infectious agents [3,8], but also for intestinal parasites. Water contamination in this country is the consequence of the discharge of untreated urban and industrial wastewater directly into rivers, lakes or seas.…”
Section: Discussionmentioning
confidence: 91%
“…In the last few years, several outbreaks of bacterial and viral infections have been reported, caused by Vibrio cholerae El Tor [3], Poliovirus [4,5], CrimeanCongo hemorrhagic fever virus [6], Rotavirus [7] and hepatitis A virus (HAV) [8]. A high endemicity level of HAV [9] and hepatitis B virus (HBV) [10,11] and recrudescence of visceral leishmaniasis [12] have also been reported.…”
Section: Introductionmentioning
confidence: 98%
“…Hepatitis A is largely endemic in Albania with an overall prevalence higher than 95% in the younger age. In autumn 1994, a cholera epidemic outbreak [Greco et al, 1995] appeared in the Southern-Central region, and in 1996 an outbreak of poliomyelitis [Divizia et al, 1999a] involved the entire country. In a survey study on drinking water quality in Tirana, Palombi et al [2001] has clearly demonstrated the high pollution of the potable water in Tirana and, indirectly, the possibility to transmit enteric viruses by contaminated water.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of studies have placed an emphasis on the epidemiology and aetiology pertaining to diarrhoeal infections among children, and there has been limited research pertaining to the epidemiology of gastroenteritis among adults within Albania (7). This is attributed to the most recent diarrhoea case management system introduced in the 1990s, which does not incorporate the modern diarrhoeal changes experienced by adults (1).…”
Section: Introductionmentioning
confidence: 99%